How "one-size-fits-all" public works contract does it better? An assessment of infrastructure provision in Italy - Massimo Finocchiaro Castro; Calogero Guccio; Ilde Rizzo (ZBW - Leibniz Information Centre for Economics, 2023)
Public infrastructure procurement is crucial as a prerequisite for public and private investments and for economic and social capital growth. However, low performance in execution severely hinders infrastructure provision and benefits delivery. One of the most sensitive phases in public infrastructure procurement is the design because of the strategic relationship that it potentially creates between procurers and contractors in the execution stage, affecting the costs and the duration of the contract. In this paper, using recent developments in non-parametric frontiers and propensity score matching, we evaluate the performance in the execution of public works in Italy. The analysis provides robust evidence of significant improvement of performance where procurers opt for design and build contracts, which lead to lower transaction costs, allowing contractors to better accommodate the project in the execution. Our findings bear considerable policy implications.
Keywords: H57; D73; O18; C14; 330; Infrastructure provision; Transaction costs economics; propensity score matching; non-parametric frontiers; public works procurement; performance; design and build contracts